A Drugethek és Ung megye betelepítése - Ferkó Okszána; Ферков Оксана; Oksana Ferkov (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"TIMPANI", 2014)
Bonyolult politikai és gazdasági körülmények között jelennek meg a Drugethek Magyarország politikai színterén és lesznek a király újításainak aktív résztvevői. A Drugethek familiáris birtokai Északkelet-Magyarország földjén terjedtek szét. Itt a Drugethek új szociális-gazdasági viszonyokat vezettek be, friss európai gondolkodás módot. A Drugethek gazdasági tevékenysége egyik oldala lett a Kárpátok túlsó oldaláról való parasztok betelepítése a saját birtokaikra, különösen Ung megyébe.

Резюме. На політичній арені Угорщини Другети з’явилися за складних політико-економічних обставин і були активними учасниками нововведень короля. Фамільні володіння графів Другетів простягалися на широких просторах північно-східної Угорщини. На них Другети запровадили нові соціально-економічні порядки, свіже європейське мислення. Одним із аспектів господарської діяльності представників роду Другетів стало заохочення переселення селян з-за Карпат на підвладні їх маєтки, особливо в Ужанщину.

Abstract. Drugeths appeared on the political scene in Hungary under difficult political and economic circumstances and they were active participants in king's innovations. Family dominions of the earls Drugeths expanded on the territories of the north-eastern Hungary. Here Drugeths introduced new social and economic orders, fresh European thinking. One of the aspects of economic activity of the representatives of Drugeth's family was to encourage the peasants to migrate from the Carpathians to their estates in Uzhanshchyna.
Другети та заселення Ужанської жупи
Drugeths and the Settlement of the Uzhanska Zhupa
https://www.kmf.uz.ua/hun114/letoltes/acta/Acta_Ac_Bereg_2014_1.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/160302
Keywords: Drugethek; Ung megye; betelepítés